MQ – MEDIALITY QUOTIENT - Juszczyk-Rygallo, Joanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The child's intellectual skills in dealing with the media are reflected in his or her media intelligence. However, the assessment of children's adaptation to life in the world of the media-sphere is difficult to make. The recognition of a pupil’s mediality, as well as its systematic development, may have a positive impact on the quality of education. Currently there are no tools in the educational system to diagnose pupils’ mediality. Therefore, there is a need to construct a useful indicator of the level of mediality, which may be a Mediality Quotient. In the cognitive perspective, it can become a tool that will contribute to the optimization of the educational process in the intellectual media environment. The aim of the article is to justify the purposefulness of conducting research on media skills of children and to present the assumptions for developing media literacy measurement techniques. The planned actions will allow to identify to what extent children acquire media skills and what is their statistical picture. The results obtained will be used to determine the coefficient enabling the measurement of media skills and their assessment in relation to the statistical average of pupils. Ultimately, the primary objective of developing a scale for measuring the Mediality Quotient of children will be achieved.